Runoff compliance for Kansas cattle feedlots - James P. Murphy; Joseph P. Harner (Kansas Agricultural Experiment Station Research Reports, 1999)
As the demand grows for cleaner water, feedlots will need to reduce and control the nutrient and sediment loading of runoff. Existing confined feedlots will need to evaluate their runoff potential. Costs of controlling the runoff must be weighed against new lot construction on an alternate location. New feedlot facilities will need to address current regulations and be designed for compliance with future regulations.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Feedlot; Runoff control; Pollution